Perspektif Mahasiswa Dan Dosen Terhadap Efektivitas Pembelajaran Daring Selama Pandemi Covid-19 - Ni Kadek Suartini (Jayapangus Press, 2020)
The occurrence of a COVID-19 pandemic resulted in a learning system changing from face-to-face learning to online learning. Many people are questioning whether the effectiveness of online learning / online to be implemented. Effectiveness in learning can be seen from the achievement of learning objectives, increasing student understanding of the material presented. The purpose of this study is to determine the effectiveness of online learning from the perspective of students and lecturers. This research is a quantitative descriptive study using a survey method conducted online by utilizing the use of Google forms. This research was conducted at the Hindu Dharma Negeri Institute of Denpasar. Primary data collection in this study was carried out by distributing questionnaires online on July 23, 2020